Deﬁning the Structure of Environmental Competence of Future Mining Engineers: ICT Approach - Моркун, Володимир; Семеріков, Сергій; Моркун, Наталія; Грищенко, Світлана; Ків, Арнольд (Pedagogy of Higher and Secondary Education, 2018)
Morkun S.V., Semerikov S.O., Morkun N.V., Hryshchenko S.M. and Kiv A.E. Deﬁning the Structure of Environmental Competence of Future Mining Engineers: ICT Approach. The object is to the reasonable selection of the ICT tools for formation of ecological competence. Pressing task is constructive and research approach to preparation of future engineers to performance of professional duties in order to make them capable to develop engineering projects independently and exercise control competently. Subject of research: the theoretical justiﬁcation of competence system of future mining engineers. Methods: source analysis on the problem of ecological competence formation. Results: deﬁning the structure of environmental competence of future mining engineers. Conclusion: the relevance of the material covered in the article, due to the need to ensure the eﬀectiveness of the educational process in the preparation of the future mining engineers.